Transition guidelines: An important step in the future care for childhood cancer survivors. A comprehensive definition as groundwork. (February 2016) - Mulder, R.L.; van der Pal, H.J.H.; Levitt, G.A.; Skinner, R.; Kremer, L.C.M.; Brown, M.C.; Bárdi, E.; Windsor, R.; Michel, G.; Frey, E.
Abstract: Evidence-based clinical practice guidelines are essential to ensure that childhood cancer survivors at risk of chronic health conditions receive effective long-term follow-up care. However, adult survivors of childhood cancer are not always engaged in recommended health promotion and follow-up practices, as many centres do not have a formal transition programme that prepares survivors and their families for successful transfer from child-centred to adult-oriented healthcare. The need for a specific pan-European guideline for the transition of care for childhood cancer survivors has been recognised. The first step is to define the concept of transition of care for survivors of childhood cancer based on existing evidence. Highlights: Adult childhood cancer survivors are not always engaged in long-term follow-up care. Failure of transition will have potentially important medical consequences. There is a need for a European transition guideline for childhood cancer survivors. The first step is to define the concept of transition for childhood cancer survivors.